INCREASING THE ROLE OF COMMUNITY GUARDIANS IN OVERCOMING BULLYING BEHAVIOR AMONG GUIDED CHILDREN IN SPECIAL DEVELOPMENT INSTITUTIONS FOR CLASS I CHILDREN IN MEDAN - Prissima, Reza; Anwar, Umar (PT Altin Riset Publishing, 2024)
Bullying in Special Child Development Institutions has become a serious concern in education and psychology. This study aims to investigate the background of bullying at the Medan Grade 1 Special Development Institute for Children and identify the factors that influence it. The research method used is a case study with a qualitative approach. Data was collected through participant observation, in-depth interviews with various related parties, and analysis of related documents. Research findings show that factors such as family dynamics, interactions with peers, and environmental conditions in special child development institutions play an important role in influencing the occurrence of bullying. Families that are less harmonious, have unhealthy interactions with peers, and have an unsupervised environment at Special Children's Development Institutions can increase the risk of bullying behavior. This research implies the need to develop holistic and evidence-based intervention strategies to prevent and handle bullying in the Special Child Development Institution environment. To create a safe, inclusive, and supportive environment for all individuals, we need to strengthen anti-bullying programs that involve all relevant stakeholders. Further research is needed to test the effectiveness of these interventions and deepen our understanding of the factors that influence the occurrence of bullying in special child development institutions.